Analisis Kualitas Layanan Akademik Madrasah Dengan Metode Servqual Pada Pendidik Dan Tenaga Kependidikan - Fina Durriyatun Bahiyyah; Udik Budi Wibowo (Universitas Kristen Satya Wacana, 2019)
This study aims to describe the quality indicators of madrasah academic services to measure the madrasah ability in providing facilities, teachers and education staff, and services that meet the student expectations with the Servqual method. This study uses a quantitative approach with analytical descriptive research. Data collecting technique used a closed questionnaire of rating scale model. Validity test uses product moment correlation and reliability test using Cronbach Alpha. The measurement indicators in this study include five aspects, namely tangibles, reliability, responsiveness, assurance and certainty, and empathy. In comprehensive terms the research results show the percentage of academic achievement service quality for teachers is 65.58%, and 58.67% in education staff. Based on five indicators, responsiveness becomes the highest achievement aspect, at 67.02%. While facilities and infrastructure, reliability, certainty and empathy assurance, still need improvement. However, overall, the academic services quality for teachers and education staff is included in the satisfying category, where the majority of teachers and education staff provide a high perception of service quality at the Thullab Foundation.